Hygienic and sanitary conditions of a confectionery located in north Bahia: a case report (Research, Society and Development, 2022)
The adoption of good practices in food and nutrition establishments is essential for the food quality control, as well as for the prevention of food outbreaks. From this perspective, the present study aimed to evaluate the hygienic-sanitary conditions of a sweet shop in the city of Juazeiro-BA, as well as to assist in the creation of an action plan in accordance with the reality of the place, aiming the improvement of the services provided. For this, the establishment was evaluated according to a checklist of good food handling and manufacturing practices, based on RDC 216/2004 and CVS 5/2013, containing 170 items distributed in 12 sections, while the classification was carried out in accordance with RDC 275/2002, following the National Health Surveillance Agency. For the microbiological analyses, samples of water, surfaces and food were collected, in which total coliforms, Escherichia coli and Staphylococcus aureus were counted using the Petrifilm analysis system. The result of the evaluation using the checklist classified the establishment as regular in accordance with current legislation, which was maintained even after a year of delivery of the action plan. Regarding microbiological analyses, all collected samples were adopted according to current regulations, however, they showed high levels of total coliforms. In view of this, it is considered that the establishment poses risks to the health of consumers, making it necessary to complete the adaptations in the establishment, in order to minimize the risks of food contamination.